The valuation of older adult homecare services under a joint medical-social budgetary perspective - Leung, Eman; Guan, Jingjing; Chu, Amanda M. Y.; Ching, Sam C. C.; Liu, Yilin; Chen, Frank Youhua (Frontiers in Public Health, 2024)
BackgroundHomecare, a cornerstone of public health, is essential for health systems to achieve the Sustainable Development Goal (SDG) of universal health coverage while maintaining its own sustainability. Notwithstanding homecare’s system-level significance, there is a lack of economic evaluations of homecare services in terms of their system-wide cost-savings. Specifically, decisions informed by a joint medical-social budgetary perspective can maximize the allocative efficiency of assigning a diverse service mix to address the complex needs of the older adult population. However, little is known regarding which homecare service mix is most system-wide cost-effective when paired with which clinical profiles.MethodsValuation of homecare’s complex interventions was performed under a generalized cost-effectiveness analysis (GCEA) framework with proportional hazard-adjusted metrics representing the common numeraire between medical and social care.ResultsInstrumental homecare, on its own or combined with either one or both of the other homecare services, yielded the greatest cost savings compared to other services or the lack thereof. When expressed under a joint medical-social budgetary perspective, instrumental homecare can reduce medical costs of HK$34.53 (US$4.40) and HK$85.03 (US$10.84) for every HK$1 (US$0.13) invested in instrumental and instrumental-restorative homecare, respectively.ConclusionInstrumental homecare can increase hospitalization-free days among community-dwelling older adult and yield significant net system-wide cost savings. Thus, the current study demonstrated the feasibility of data-informed decision-making in system-wide resource allocation under a joint medical-social budget perspective.